178k views
1 vote
. if f(x+3)=x+6 find inverse of function f(x)​

User Eoredson
by
4.1k points

2 Answers

6 votes

Answer:

The answer is g(x)=x-3

Explanation:

If f(x+3)=x+6 find inverse of function f(x).

Let u=x+3, then x=u-3.

Make this substitution into our given:

f(u)=(u-3)+6

Simplify:

f(u)=u+(-3+6)

f(u)=u+3

Now let's find the inverse of f(u)...

Or if you prefer rename the variable...

f(x)=x+3

Now, we are going to solve y=x+3 for x.

Subtracting 3 on both sides gives: y-3=x.

Interchange x and y: x-3=y.

So the inverse of f(x)=x+3 is g(x)=x-3.

User JJ Du Plessis
by
4.7k points
3 votes

Answer:

g(x)=x-3

Problem:

If f(x+3)=x+6 find inverse of function f(x).

Explanation:

Let u=x+3, then x=u-3.

Make this substitution into our given:

f(u)=(u-3)+6

Simplify:

f(u)=u+(-3+6)

f(u)=u+3

Now let's find the inverse of f(u)...

Or if you prefer rename the variable...

f(x)=x+3

Now, we are going to solve y=x+3 for x.

Subtracting 3 on both sides gives: y-3=x.

Interchange x and y: x-3=y.

So the inverse of f(x)=x+3 is g(x)=x-3.

User Jasoni
by
4.7k points